2007
DOI: 10.1177/0269881106075588
|View full text |Cite
|
Sign up to set email alerts
|

Review: Serotonin by stress interaction: a susceptibility factor for the development of depression?

Abstract: A genetic predisposition to depression may be a potential risk factor in the development of depression. Although the neurobiological equivalent of the predisposition remains unclear, it seems as though the brain serotonin (5-HT) system plays an important mediating role. Therefore, individuals with a family history of depression (FH+) may be more likely to develop depression due to an innate vulnerability related to altered serotonergic neurotransmission in the brain. A major problem, however, is that the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 85 publications
8
67
0
1
Order By: Relevance
“…Acute stress increases 5-HT neurotransmission (Davis et al 1995;De Kloet et al 1982, 1983, which promotes stress adaptation by mediating negative feedback control of cortisol on the HPA axis (Nuller and Ostroumova 1980;Van Praag 2004). In accord with the current findings, s allele carriers are thought to be 5-HT vulnerable and to be susceptible to depression symptoms particularly in the face of stress (Caspi et al 2003;Firk and Markus 2007;Van Praag 2004). Although hypothetically, stress and enhanced HPA activation, particularly in s allele carriers, may further undermine 5-HT function, which then may lead to reduced stress coping and subsequently result in negative mood (e.g., Dayan and Huys 2008;Firk and Markus 2007;Van Praag 2004).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Acute stress increases 5-HT neurotransmission (Davis et al 1995;De Kloet et al 1982, 1983, which promotes stress adaptation by mediating negative feedback control of cortisol on the HPA axis (Nuller and Ostroumova 1980;Van Praag 2004). In accord with the current findings, s allele carriers are thought to be 5-HT vulnerable and to be susceptible to depression symptoms particularly in the face of stress (Caspi et al 2003;Firk and Markus 2007;Van Praag 2004). Although hypothetically, stress and enhanced HPA activation, particularly in s allele carriers, may further undermine 5-HT function, which then may lead to reduced stress coping and subsequently result in negative mood (e.g., Dayan and Huys 2008;Firk and Markus 2007;Van Praag 2004).…”
Section: Discussionsupporting
confidence: 83%
“…In accord with the current findings, s allele carriers are thought to be 5-HT vulnerable and to be susceptible to depression symptoms particularly in the face of stress (Caspi et al 2003;Firk and Markus 2007;Van Praag 2004). Although hypothetically, stress and enhanced HPA activation, particularly in s allele carriers, may further undermine 5-HT function, which then may lead to reduced stress coping and subsequently result in negative mood (e.g., Dayan and Huys 2008;Firk and Markus 2007;Van Praag 2004). In further support, Gotlib et al (2008) found that only girls homozygous for the s allele showed a cortisol response following acute stress exposure, which also supports the hypothesis that 5-HTTLPR affects HPA activity and hence, stress reactivity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Complex interactions between genetic susceptibility to serotonergic and noradrenergic system dysfunction and stress-related changes in the HPA axis have been implicated in the etiology of depression (Firk, Markus, Firk, & Markus, 2007;Porter et al, 2004), and psychopharmacological treatment studies support the role of reduced neurotransmission of serotonin and norepinephrine in the pathophysiology of GAD (Nutt, Argyropoulos, Hood, & Potokar, 2006). Despite the extensive body of research linking corticotrophin-releasing factor and the HPA axis to depression (Hankin, Badanes, Abela, & Watamura, 2010;Nemeroff & Vale, 2005;Wardenaar, et al, 2011), almost 24 no research has investigated the role of the HPA axis in the etiology of GAD separate from the INT-FA anxiety disorders.…”
mentioning
confidence: 99%